Inter-subject transfer learning for EEG-based mental fatigue recognition - Liu, Yisi; Lan, Zirui; Cui, Jian; Sourina, Olga; Müller-Wittig, Wolfgang (Advanced engineering informatics, 2020)
Mental fatigue is one of the major factors leading to human errors. To avoid failures caused by mental fatigue, researchers are working on ways to detect/monitor fatigue using different types of signals. Electroencephalography (EEG) signal is one of the most popular methods to recognize mental fatigue since it directly measures the neurophysiological activities in the brain. Current EEG-based fatigue recognition algorithms are usually subject-specific, which means a classifier needs to be trained per subject. However, as fatigue may need a relatively long period to induce, collecting training data from each new user could be time-consuming and troublesome. Calibration-free methods are desired but also challenging since significant variability of physiological signals exists among different subjects. In this paper, we proposed algorithms using inter-subject transfer learning for EEG-based mental fatigue recognition, which did not need a calibration. To explore the influence of the number of EEG channels on the algorithms’ accuracy, we also compared the cases of using one channel only and multiple channels. Random forest was applied to choose the channel that has the most distinguishable features. A public EEG fatigue dataset recorded during driving was used to validate the algorithms. EEG data from 11 subjects were selected from the dataset and leave-one-subject-out cross-validation was employed. The channel from the occipital lobe is selected when only one channel is desired. The proposed transfer learning-based algorithms using Maximum Independence Domain Adaptation (MIDA) achieved an accuracy of 73.01% with all thirty channels, and using Transfer Component Analysis (TCA) achieved 68.00% with the one selected channel.